Bornite / ferric oxide heterojunction photo-Fenton catalyst and preparation method and application thereof

By using the heterojunction photofenton catalyst of tetrachomatite/ferric oxide, the problem of difficulty in recovering catalysts in the existing photofenton system is solved, and catalytic activity and organic pollutant removal efficiency are improved, achieving efficient removal effect in water treatment.

CN119016068BActive Publication Date: 2025-04-25SHAANXI UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411127539.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-16
Publication Date
2025-04-25
Estimated Expiration
2044-08-16

AI Technical Summary

Technical Problem

The catalysts are difficult to recover in the existing photofenton system, and the iron-cycling efficiency of iron-based catalysts is low, which limits the application of this technology in water treatment.

Method used

The heterojunction photofenton catalyst of Cu5FeS4 nanosheets was used to form an S-shaped heterostructure with the γ-Fe2O3 nanoparticles, which had magnetic separation characteristics and dual active sites, and were prepared by hydrothermal method and high-temperature calcination.

Benefits of technology

The catalytic activity of the catalyst and the activation efficiency of H2O2 are improved, and the circulation of Fe(II)/Fe(II) and Cu(II)/Cu(I) is promoted, and the rapid removal of organic pollutants in the water is achieved, and the catalyst can be effectively recovered.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119016068B_ABST
    Figure CN119016068B_ABST
Patent Text Reader

Abstract

The present invention discloses a bornite / ferric oxide heterojunction photo-Fenton catalyst, a preparation method and an application, comprising dissolving a copper salt in deionized water, adding polyvinyl pyrrolidone to dissolve to obtain a mixed solution, dissolving thiourea in deionized water, adding the dissolved solution to the mixed solution and stirring, and then adding an iron salt and stirring to obtain a mixed solution; transferring the mixed solution to a polytetrafluoroethylene liner for hydrothermal reaction, cooling to obtain a reaction product; and centrifuging, washing, drying, calcining and grinding the reaction product. The catalyst of the present invention can accelerate the circulation of Fe(III) / Fe(II) and Cu(II) / Cu(I), improve the catalytic activity of the photo-Fenton system, and realize the rapid removal of organic pollutants in water. The photo-Fenton performance of organic pollutants is excellent, and the catalyst has magnetic separation characteristics, and can be effectively separated and recovered.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalysts, and in particular relates to a bornite / ferric oxide heterojunction photo-Fenton catalyst, a preparation method of the catalyst, and an application of the catalyst. Background Art

[0002] With the rapid development of industrialization and economy, water pollution has become increasingly prominent, posing a serious threat to human production, life and environmental quality. Therefore, the development of green and efficient water treatment technology is of great significance for the effective removal of organic pollutants in water. Fenton oxidation is a commonly used advanced oxidation technology for water treatment. It uses hydrogen peroxide (H 2 O 2 ) reacts with ferrous iron (Fe(Ⅱ)) under acidic conditions to produce highly oxidizing hydroxyl radicals (·OH), which oxidize and decompose organic pollutants into CO 2 , H 2 Non-toxic and harmless small molecules such as O have attracted much attention in the treatment of organic wastewater. Compared with the traditional homogeneous Fenton, the iron-based heterogeneous Fenton reaction can greatly reduce the amount of iron sludge produced, and the catalyst can be recycled and reused, which effectively overcomes many shortcomings of the homogeneous Fenton system. However, the iron cycle (Fe(III) / Fe(II)) efficiency of most iron-based catalysts used in the heterogeneous Fenton reaction is still low, which in turn limits and hinders the widespread application of this technology in actual water treatment. Introducing a light source into the heterogeneous Fenton reaction and constructing a photo-Fenton system with photocatalytic coupling Fenton, the reductive photogenerated electrons generated by photocatalysis can effectively promote the cycle of Fe(III) / Fe(II), improve the catalytic activity of the catalyst and H 2 O 2 Although the activation efficiency is high, there are still problems such as high recombination rate of photogenerated electron-hole pairs and complex catalyst recovery process. Summary of the invention

[0003] The first purpose of the present invention is to provide a bornite / ferric oxide heterojunction photo-Fenton catalyst, which solves the problem that the catalyst in the existing photo-Fenton system is difficult to recover.

[0004] The second object of the present invention is to provide a method for preparing a bornite / ferric oxide heterojunction photo-Fenton catalyst.

[0005] The third object of the present invention is to provide the application of bornite / ferric oxide heterojunction photo-Fenton catalyst.

[0006] The first technical solution adopted by the present invention is that the bornite / ferric oxide heterojunction photo-Fenton catalyst is a photo-Fenton catalyst with an S-type heterostructure, and the bornite / ferric oxide heterojunction photo-Fenton catalyst has a magnetic separation characteristic.

[0007] The first technical solution of the present invention is also characterized in that:

[0008] The structure of the bornite / Fe2O3 heterojunction photo-Fenton catalyst is Cu 5 FeS 4 The nanosheets self-assembled into flower-like microspheres with a diameter of 3 μm-10 μm. 5 FeS 4 The surface of the nanosheets is immobilized with γ-Fe with a size of 5nm-15nm 2 O 3 Nanoparticles.

[0009] The ratio of Cu(Ⅰ):Cu(Ⅱ) in the bornite / ferric oxide heterojunction photo-Fenton catalyst is 1:1-1:3, and the ratio of Fe(Ⅱ):Fe(Ⅲ) is 1:0.5-1:2.

[0010] The second technical solution adopted by the present invention is a method for preparing a bornite / ferric oxide heterojunction photo-Fenton catalyst, which is specifically implemented according to the following steps:

[0011] Step 1, dissolving copper salt in deionized water, and adding polyvinyl pyrrolidone to obtain a mixed solution, then dissolving thiourea in deionized water, adding the dissolved thiourea to the mixed solution and stirring, and then adding iron salt and stirring to obtain a mixed solution;

[0012] Step 2, transferring the mixed solution to a polytetrafluoroethylene liner for hydrothermal reaction, and cooling to obtain a reaction product;

[0013] Step 3: centrifuge, wash, dry, calcine and grind the reaction product obtained in step 2 to obtain a bornite / ferric oxide heterojunction photo-Fenton catalyst.

[0014] The second technical solution of the present invention is also characterized in that:

[0015] The copper salt in step 1 is one of copper acetate, copper chloride, copper nitrate or copper sulfate, and the iron salt is one of iron acetate, iron chloride, iron nitrate or iron sulfate.

[0016] In step 1, the molar ratio of copper salt to iron salt is 1:1-1:4, the mass of polyvinyl pyrrolidone is 0.02g-0.08g, the molar mass of thiourea is 28mmol-40mmol, and the stirring time for both times is 20min-60min.

[0017] In step 2, the hydrothermal reaction temperature is 120°C-180°C, and the reaction time is 6h-12h.

[0018] In step 3, the product is washed with anhydrous ethanol and deionized water for 3-4 times respectively, the freeze-drying time is 12h-24h, the calcination temperature is 500°C-800°C, and the calcination time is 2h-4h.

[0019] The third technical solution adopted by the present invention is the use of bornite / ferric oxide heterojunction photo-Fenton catalyst in photo-Fenton degradation of organic pollutants in water.

[0020] The third technical solution of the present invention is also characterized in that:

[0021] The organic pollutant was one of sulfamethoxazole, carbamazepine, phenol or 4-nitrophenol.

[0022] The beneficial effects of the present invention are:

[0023] The present invention is bornite / ferric oxide (Cu 5 FeS 4 / γ-Fe 2 O 3 ) The heterojunction photo-Fenton catalyst has abundant copper-iron dual active sites, which can activate H 2 O 2 ; Bornite / Fe2O3 heterojunction photo-Fenton catalyst has strong visible light absorption ability and can generate a large number of photogenerated electrons; Cu 5 FeS 4 With γ-Fe 2 O 3 The formed S-type heterostructure is beneficial to the separation of photogenerated electron-hole pairs, promoting the reduction of Fe(Ⅲ) to Fe(Ⅱ) and Cu(Ⅱ) to Cu(Ⅰ) by photogenerated electrons, and accelerating the circulation of Fe(Ⅲ) / Fe(Ⅱ) and Cu(Ⅱ) / Cu(Ⅰ); the bornite / ferric oxide heterojunction photo-Fenton catalyst has magnetic separation characteristics and can be effectively separated and recovered; the photo-Fenton degradation performance of organic pollutants is excellent. Within 3 minutes, 1 mg / L-20 mg / L of organic pollutants (sulfamethoxazole, carbamazepine, phenol or 4-nitrophenol) can be completely degraded, and the total organic carbon removal rate can reach 80% or more in 30 minutes. The method for preparing a bornite / ferric oxide heterojunction photo-Fenton catalyst of the present invention successfully prepares a bornite / ferric oxide heterojunction photo-Fenton catalyst with dual active sites by a simple hydrothermal method and high-temperature calcination, the separation efficiency of photogenerated electron-hole pairs is greatly improved, the circulation of Fe(III) / Fe(II) and Cu(II) / Cu(I) is promoted, the catalytic activity of the photo-Fenton system is improved, and the rapid removal of organic pollutants in water is realized, the preparation process is simple and controllable, the raw materials are cheap and easily available, and the preparation cost is low. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1is an X-ray diffraction spectrum of the bornite / ferric oxide heterojunction photo-Fenton catalyst of the present invention;

[0025] Figure 2 This is a scanning electron microscope image of the bornite / ferric oxide heterojunction photo-Fenton catalyst of the present invention;

[0026] Figure 3 It is the ultraviolet-visible diffuse reflectance image of the bornite / ferric oxide heterojunction photo-Fenton catalyst of the present invention;

[0027] Figure 4 The bornite / ferric oxide heterojunction photo-Fenton catalyst of the present invention and Cu 5 FeS 4 ,γ-Fe 2 O 3 Comparison of degradation efficiency of sulfamethoxazole in photo-Fenton catalytic degradation;

[0028] Figure 5 This is a photo-Fenton degradation performance diagram of the bornite / ferric oxide heterojunction photo-Fenton catalyst of the present invention for different organic pollutants;

[0029] Figure 6 Graph showing the total organic carbon removal rate of different organic pollutants by the bornite / ferric oxide heterojunction photo-Fenton catalyst of the present invention;

[0030] Figure 7 This is a magnetic test diagram of the bornite / ferric oxide heterojunction photo-Fenton catalyst of the present invention. DETAILED DESCRIPTION

[0031] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0032] The present invention is bornite / ferric oxide (Cu 5 FeS 4 / γ-Fe 2 O 3 ) The preparation method of the heterojunction photo-Fenton catalyst is specifically implemented according to the following steps:

[0033] Step 1, dissolving copper salt in deionized water, and adding polyvinyl pyrrolidone to obtain a mixed solution, then dissolving thiourea in deionized water, adding the dissolved thiourea to the mixed solution and stirring, and then adding iron salt and stirring to obtain a mixed solution;

[0034] The copper salt in step 1 is one of copper acetate, copper chloride, copper nitrate or copper sulfate, and the iron salt is one of iron acetate, iron chloride, iron nitrate or iron sulfate;

[0035] In step 1, the molar ratio of copper salt to iron salt is 1:1-1:4, the mass of polyvinyl pyrrolidone is 0.02g-0.08g, the molar mass of thiourea is 28mmol-40mmol, and the stirring time for both times is 20min-60min;

[0036] Step 2, transferring the mixed solution to a polytetrafluoroethylene liner for hydrothermal reaction, and cooling to obtain a reaction product;

[0037] In step 2, the hydrothermal reaction temperature is 120°C-180°C, and the reaction time is 6h-12h;

[0038] Step 3, centrifuging, washing, drying, calcining and grinding the reaction product obtained in step 2 to obtain a bornite / ferric oxide heterojunction photo-Fenton catalyst;

[0039] In step 3, the product is washed with anhydrous ethanol and deionized water for 3-4 times respectively, the freeze-drying time is 12h-24h, the calcination temperature is 500°C-800°C, and the calcination time is 2h-4h.

[0040] The structure of the bornite / ferric oxide heterojunction photo-Fenton catalyst prepared by the present invention is Cu 5 FeS 4 Flower-like microspheres with a diameter of 3 μm-10 μm formed by self-assembly of nanosheets, Cu 5 FeS 4 The surface of the nanosheets is immobilized with γ-Fe with a size of 5nm-15nm. 2 O 3 Nanoparticles. The ratio of Cu(Ⅰ):Cu(Ⅱ) in the bornite / ferric oxide heterojunction photo-Fenton catalyst is 1:1-1:3, the ratio of Fe(Ⅱ):Fe(Ⅲ) is 1:0.5-1:2, and it has an S-type heterostructure and magnetic separation characteristics.

[0041] Application of bornite / ferric oxide heterojunction photo-Fenton catalyst in photo-Fenton degradation of organic pollutants in water; the organic pollutant is one of sulfamethoxazole, carbamazepine, phenol or 4-nitrophenol.

[0042] Example 1

[0043] The method for preparing the bornite / ferric oxide heterojunction photo-Fenton catalyst of the present invention is specifically implemented according to the following steps:

[0044] Step 1, dissolve copper acetate in 20 mL of deionized water, and add 0.06 g of polyvinyl pyrrolidone until it is completely dissolved to obtain a mixed solution, dissolve 36 mmol of thiourea in 35 mL of deionized water, and pour it into the mixed solution and stir for 20 minutes; finally, add ferric acetate in a molar ratio of 1:2 to copper acetate to the above solution and stir for 20 minutes to obtain a mixed solution;

[0045] Step 2, transferring the mixed solution to a polytetrafluoroethylene liner, performing a hydrothermal reaction at a temperature of 160° C. for 10 h, and cooling to obtain a reaction product;

[0046] Step 3: After centrifuging the reaction product obtained in step 2, wash it with anhydrous ethanol and deionized water for three times respectively, freeze-dry it for 24 hours, calcine it at 600° C. for 2 hours, and finally grind it to obtain a bornite / ferric oxide heterojunction photo-Fenton catalyst.

[0047] The structure of the bornite / ferric oxide heterojunction photo-Fenton catalyst in this embodiment is Cu 5 FeS 4 The nanosheets self-assembled into flower-like microspheres with a diameter of 3 μm, and Cu 5 FeS 4 The surface of the nanosheets is immobilized with γ-Fe with a size of 5 nm. 2 O 3 Nanoparticles. The ratio of Cu(Ⅰ):Cu(Ⅱ) in the bornite / ferric oxide heterojunction photo-Fenton catalyst is 1:1.5, and the ratio of Fe(Ⅱ):Fe(Ⅲ) is 1:0.5.

[0048] The X-ray diffraction spectrum of the bornite / ferric oxide heterojunction photo-Fenton catalyst obtained in this example is shown in Figure 1 The XRD spectrum shows that the characteristic diffraction peaks at 30.2°, 35.6°, 43.3°, 57.2° and 62.9° are derived from the cubic phase γ-Fe 2 O 3 The (220), (311), (400), (511) and (440) crystal planes of CuO2 and CuO2 are the main sources of the other characteristic peaks. 5 FeS 4 .

[0049] The bornite / ferric oxide heterojunction photo-Fenton catalyst obtained in this example was used to degrade sulfamethoxazole: a 300 W xenon lamp (λ>420 nm) was used as the excitation light source, the reaction temperature was 25° C., the concentration of sulfamethoxazole in the aqueous solution was 20 mg / L, the concentration of the bornite / ferric oxide heterojunction photo-Fenton catalyst in the reaction system was 200 mg / L, and H 2 O 2 The concentration in the aqueous solution was 3 mmol / L. The mixed solution of bornite / ferric oxide heterojunction photo-Fenton catalyst and sulfamethoxazole was kept in the dark for 30 min until the adsorption-desorption equilibrium was reached. The light source was turned on, and the irradiation amount per unit area of ​​the solution surface was 250 m-W / cm 2 , stirred for 2 minutes, the degradation rate of sulfamethoxazole was measured to be 100%, and the total organic carbon removal rate was measured to be 82% after 30 minutes.

[0050] The photo-Fenton degradation of sulfamethoxazole by the bornite / ferric oxide heterojunction photo-Fenton catalyst obtained in this example is shown in FIG. Figure 4 It can be seen that the degradation rate of sulfamethoxazole by the bornite / Fe2O3 heterojunction photo-Fenton catalyst was 100% within 2 min, which was comparable to that of the pure Cu 5 FeS 4 and γ-Fe 2 O 3 Compared with the degradation effect of organic matter, its photo-Fenton degradation effect is greatly improved.

[0051] The magnetic separation experimental results of the bornite / iron oxide heterojunction photo-Fenton catalyst obtained in this example are shown in Figure 7 It can be seen that the bornite / Fe2O3 heterojunction photo-Fenton catalyst has good magnetic separation properties, which is beneficial to the recovery and reuse of the catalyst.

[0052] Example 2

[0053] The method for preparing the bornite / ferric oxide heterojunction photo-Fenton catalyst of the present invention is specifically implemented according to the following steps:

[0054] Step 1, dissolve cupric chloride in 20 mL of deionized water, and add 0.02 g of polyvinyl pyrrolidone until it is completely dissolved to obtain a mixed solution, dissolve 28 mmol of thiourea in 35 mL of deionized water, and pour it into the mixed solution and stir for 30 minutes; finally, add ferric chloride in a molar ratio of 1:1 to cupric chloride to the above solution and stir for 30 minutes to obtain a mixed solution;

[0055] Step 2, transferring the mixed solution to a polytetrafluoroethylene liner, performing a hydrothermal reaction at a temperature of 120° C. for 12 hours, and cooling to obtain a reaction product;

[0056] Step 3: After centrifuging the reactant obtained in step 2, wash it with anhydrous ethanol and deionized water for 4 times respectively, freeze-dry it for 12 hours, calcine it at 500° C. for 4 hours, and finally grind it to obtain a bornite / ferric oxide heterojunction photo-Fenton catalyst.

[0057] The structure of the bornite / ferric oxide heterojunction photo-Fenton catalyst in this embodiment is Cu 5 FeS 4 The nanosheets self-assembled into flower-like microspheres with a diameter of 5 μm, and Cu 5 FeS 4 The surface of the nanosheets is immobilized with γ-Fe with a size of 10 nm. 2 O 3 Nanoparticles. The ratio of Cu(Ⅰ):Cu(Ⅱ) in the bornite / ferric oxide heterojunction photo-Fenton catalyst is 1:1, and the ratio of Fe(Ⅱ):Fe(Ⅲ) is 1:1.5.

[0058] The scanning electron microscope of the bornite / ferric oxide heterojunction photo-Fenton catalyst obtained in this example shows Figure 2 From the scanning electron microscope image, it can be seen that the surface morphology of the bornite / Fe2O3 material is composed of Cu 5 FeS 4 The nanosheets self-assembled into a flower-like microsphere structure with a diameter of about 5 μm, and γ-Fe with a size of about 10 nm was immobilized on the surface of the nanosheets. 2 O 3 Particles.

[0059] The bornite / ferric oxide heterojunction photo-Fenton catalyst obtained in this example was used to degrade carbamazepine: a 300 W xenon lamp (λ>420 nm) was used as the excitation light source, the reaction temperature was 25° C., the concentration of carbamazepine in the aqueous solution was 20 mg / L, the concentration of the bornite / ferric oxide heterojunction photo-Fenton catalyst in the reaction system was 200 mg / L, and the H 2 O 2 The concentration in aqueous solution was 3 mmol / L. The mixed solution of bornite / ferric oxide heterojunction photo-Fenton catalyst and carbamazepine was kept in dark conditions for 30 min until the adsorption-desorption equilibrium was reached. The light source was turned on, and the irradiation of the light source per unit area on the solution surface was 250 mW / cm 2 , stirred for 3 minutes, the carbamazepine degradation rate was measured to be 100%, and the total organic carbon removal rate was measured to be 80% after 30 minutes.

[0060] Example 3

[0061] The method for preparing the bornite / ferric oxide heterojunction photo-Fenton catalyst of the present invention is specifically implemented according to the following steps:

[0062] Step 1, dissolving copper nitrate in 20 mL of deionized water, and adding 0.04 g of polyvinyl pyrrolidone until completely dissolved to obtain a mixed solution, dissolving 32 mmol of thiourea in 35 mL of deionized water, and pouring into the mixed solution and stirring for 40 minutes; finally, adding ferric nitrate in a molar ratio of 1:3 to copper nitrate to the above solution and stirring for 40 minutes to obtain a mixed solution;

[0063] Step 2, transferring the mixed solution to a polytetrafluoroethylene liner, performing a hydrothermal reaction at a temperature of 180° C. for 6 hours, and cooling to obtain a reaction product;

[0064] Step 3: After centrifuging the reaction product obtained in step 2, wash it with anhydrous ethanol and deionized water for three times respectively, freeze-dry it for 16 hours, calcine it at 700° C. for 3 hours, and finally grind it to obtain a bornite / ferric oxide heterojunction photo-Fenton catalyst.

[0065] The structure of the bornite / ferric oxide heterojunction photo-Fenton catalyst in this embodiment is Cu 5 FeS 4 The nanosheets self-assembled into flower-like microspheres with a diameter of 7 μm, and Cu 5 FeS 4 The surface of the nanosheets is immobilized with γ-Fe with a size of 7 nm. 2 O 3 Nanoparticles. The ratio of Cu(Ⅰ):Cu(Ⅱ) in the bornite / ferric oxide heterojunction photo-Fenton catalyst is 1:2, and the ratio of Fe(Ⅱ):Fe(Ⅲ) is 1:1.

[0066] The UV-visible diffuse reflectance of the bornite / ferric oxide heterojunction photo-Fenton catalyst obtained in this example is shown in FIG. Figure 3 It can be seen that the bornite / Fe2O3 heterojunction photo-Fenton catalyst has a strong visible light absorption ability.

[0067] The bornite / ferric oxide heterojunction photo-Fenton catalyst obtained in this example was used to degrade phenol: a 300 W xenon lamp (λ>420 nm) was used as the excitation light source, the reaction temperature was 25° C., the concentration of phenol in the aqueous solution was 20 mg / L, the concentration of the bornite / ferric oxide heterojunction photo-Fenton catalyst in the reaction system was 200 mg / L, and the H 2 O 2 The concentration in the aqueous solution is 3 mmol / L. The mixed solution of bornite / ferric oxide heterojunction photo-Fenton catalyst and phenol is kept in the dark for 30 min until the adsorption-desorption equilibrium is reached. The light source is turned on, and the irradiation of the light source per unit area on the solution surface is 250 mW / cm 2 , stirred for 3 minutes, the phenol degradation rate was measured to be 100%, and the total organic carbon removal rate was measured to be 100% after 30 minutes.

[0068] Example 4

[0069] The method for preparing the bornite / ferric oxide heterojunction photo-Fenton catalyst of the present invention is specifically implemented according to the following steps:

[0070] Step 1, dissolve copper sulfate in 20 mL of deionized water, and add 0.08 g of polyvinyl pyrrolidone until it is completely dissolved to obtain a mixed solution, dissolve 40 mmol of thiourea in 35 mL of deionized water, and pour it into the mixed solution and stir for 60 minutes; finally, add iron sulfate in a molar ratio of 1:4 to copper sulfate to the above solution and stir for 60 minutes to obtain a mixed solution;

[0071] Step 2, transferring the mixed solution to a polytetrafluoroethylene liner, performing a hydrothermal reaction at a temperature of 140° C. for 8 h, and cooling to obtain a reaction product;

[0072] Step 3: After centrifuging the reaction product obtained in step 2, wash it with anhydrous ethanol and deionized water for 4 times respectively, freeze-dry it for 20 hours, calcine it at 800° C. for 2 hours, and finally grind it to obtain a bornite / ferric oxide heterojunction photo-Fenton catalyst.

[0073] The structure of the bornite / ferric oxide heterojunction photo-Fenton catalyst in this embodiment is Cu 5 FeS 4 The nanosheets self-assembled into flower-like microspheres with a diameter of 10 μm, and Cu 5 FeS 4 The surface of the nanosheets is immobilized with γ-Fe with a size of 15 nm. 2 O 3 Nanoparticles. The ratio of Cu(Ⅰ):Cu(Ⅱ) in the bornite / Fe(III) heterojunction photo-Fenton catalyst is 1:3, and the ratio of Fe(Ⅱ):Fe(Ⅲ) is 1:2.

[0074] The bornite / ferric oxide heterojunction photo-Fenton catalyst obtained in this example was used to degrade 4-nitrophenol: a 300 W xenon lamp (λ>420 nm) was used as the excitation light source, the reaction temperature was 25° C., the concentration of 4-nitrophenol in the aqueous solution was 20 mg / L, the concentration of the bornite / ferric oxide heterojunction photo-Fenton catalyst in the reaction system was 200 mg / L, and the H 2 O 2 The concentration in the aqueous solution was 3 mmol / L. The mixed solution of bornite / ferric oxide heterojunction photo-Fenton catalyst and 4-nitrophenol was kept in the dark for 30 min until the adsorption-desorption equilibrium was reached. The light source was turned on, and the irradiation of the light source per unit area on the solution surface was 250 mW / cm 2 , stirred for 3 minutes, the degradation rate of 4-nitrophenol was measured to be 100%, and the total organic carbon removal rate was measured to be 92% after 30 minutes.

[0075] The photo-Fenton degradation effects of the bornite / ferric oxide heterojunction catalysts obtained in Examples 1-4 on sulfamethoxazole, carbamazepine, phenol or 4-nitrophenol are shown in Table 1. Figure 5 It can be seen that the degradation rate of the above organic pollutants by the bornite / ferric oxide heterojunction photo-Fenton catalyst is 100% within 3 minutes.

[0076] The total organic carbon removal rates of bornite / ferric oxide heterojunction photo-Fenton catalysts obtained in Examples 1-4 for sulfamethoxazole, carbamazepine, phenol or 4-nitrophenol were shown in Table 1. Figure 6 It can be seen that the total organic carbon removal rate of the catalyst for the above-mentioned different organic pollutants can reach 80% or above in 30 minutes, and it has a good mineralization effect.

[0077] Through the above method, the bornite / ferric oxide heterojunction photo-Fenton catalyst of the present invention has abundant copper and iron dual active sites, both of which can activate H 2 O 2 ; Bornite / Fe2O3 heterojunction photo-Fenton catalyst has strong visible light absorption ability and can generate a large number of photogenerated electrons; Cu 5 FeS 4 With γ-Fe 2 O 3 The formed S-type heterostructure is beneficial to the separation of photogenerated electron-hole pairs, promoting the reduction of Fe(Ⅲ) to Fe(Ⅱ) and Cu(Ⅱ) to Cu(Ⅰ) by photogenerated electrons, and accelerating the circulation of Fe(Ⅲ) / Fe(Ⅱ) and Cu(Ⅱ) / Cu(Ⅰ); the bornite / ferric oxide heterojunction photo-Fenton catalyst has magnetic separation characteristics and can be effectively separated and recovered; the photo-Fenton degradation performance of organic pollutants is excellent. Within 3 minutes, 1 mg / L-20 mg / L of organic pollutants (sulfamethoxazole, carbamazepine, phenol or 4-nitrophenol) can be completely degraded, and the total organic carbon removal rate can reach 80% or more in 30 minutes. The bornite / ferric oxide heterojunction photo-Fenton catalyst of the present invention successfully prepares the bornite / ferric oxide heterojunction photo-Fenton catalyst with double active sites through two steps of a simple hydrothermal method and high-temperature calcination, the separation efficiency of photogenerated electron-hole pairs is greatly improved, the circulation of Fe(III) / Fe(II) and Cu(II) / Cu(I) is promoted, the catalytic activity of the photo-Fenton system is improved, and the rapid removal of organic pollutants in water is realized; the preparation process is simple and controllable, the raw materials are cheap and easily available, and the preparation cost is low.

Claims

1. Bornite / Fe2O3 heterojunction photo-Fenton catalyst, characterized in that: The bornite / ferric oxide Cu5FeS4 / γ-Fe2O3 heterojunction photo-Fenton catalyst is a photo-Fenton catalyst with an S-type heterostructure, and the bornite / ferric oxide heterojunction photo-Fenton catalyst has magnetic separation characteristics; The structure of the bornite / ferric oxide heterojunction photo-Fenton catalyst is: flower-shaped microspheres with a diameter of 3µm-10µm formed by self-assembly of Cu5FeS4 nanosheets, and γ-Fe2O3 nanoparticles with a size of 5nm-15nm are immobilized on the surface of the Cu5FeS4 nanosheets.

2. The bornite / ferric oxide heterojunction photo-Fenton catalyst according to claim 1, characterized in that: In the bornite / ferric oxide heterojunction photo-Fenton catalyst, the ratio of Cu(I):Cu(II) is 1:1-1:3, and the ratio of Fe(II):Fe(III) is 1:0.5-1:

2.

3. The method for preparing the bornite / ferric oxide heterojunction photo-Fenton catalyst according to any one of claims 1 to 2, characterized in that: Follow the steps below to implement it: Step 1, dissolving copper salt in deionized water, and adding polyvinyl pyrrolidone to obtain a mixed solution, then dissolving thiourea in deionized water, adding the dissolved thiourea to the mixed solution and stirring, and then adding iron salt and stirring to obtain a mixed solution; Step 2, transferring the mixed solution to a polytetrafluoroethylene liner for hydrothermal reaction, and cooling to obtain a reaction product; Step 3: centrifuge, wash, dry, calcine and grind the reaction product obtained in step 2 to obtain a bornite / ferric oxide heterojunction photo-Fenton catalyst.

4. The method for preparing the bornite / ferric oxide heterojunction photo-Fenton catalyst according to claim 3, characterized in that: The copper salt in step 1 is one of copper acetate, copper chloride, copper nitrate or copper sulfate, and the iron salt is one of iron acetate, iron chloride, iron nitrate or iron sulfate.

5. The method for preparing the bornite / ferric oxide heterojunction photo-Fenton catalyst according to claim 3, characterized in that: In the step 1, the molar ratio of the copper salt to the iron salt is 1:1-1:4, the mass of polyvinyl pyrrolidone is 0.02g-0.08g, the molar mass of thiourea is 28mmol-40mmol, and the stirring time for both times is 20min-60min.

6. The method for preparing the bornite / ferric oxide heterojunction photo-Fenton catalyst according to claim 3, characterized in that: The hydrothermal reaction temperature in step 2 is 120° C.-180° C., and the reaction time is 6 h-12 h.

7. The method for preparing the bornite / ferric oxide heterojunction photo-Fenton catalyst according to claim 3, characterized in that: In step 3, the mixture is washed with anhydrous ethanol and deionized water for 3-4 times respectively, the freeze-drying time is 12h-24h, the calcination temperature is 500°C-800°C, and the calcination time is 2h-4h.

8. Use of the bornite / ferric oxide heterojunction photo-Fenton catalyst according to any one of claims 1-2 in photo-Fenton degradation of organic pollutants in water.

9. Use of the bornite / ferric oxide heterojunction photo-Fenton catalyst according to claim 8 in photo-Fenton degradation of organic pollutants in water, characterized in that: The organic pollutant is one of sulfamethoxazole, carbamazepine, phenol or 4-nitrophenol.

Citation Information

Patent Citations

  • Preparation method of CdS / Cu5FeS4 heterojunction semiconductor photocatalyst

    CN113134367A

  • Preparation and application of CdS / Cu5FeS4 / RGO nano-composite photocatalyst

    CN113134368A